Analysis of Vitamin C in Sambal Orange and Passion Fruit Syrup Using Iodometric Titration Method - Lusiana Lusiana; Nur Fitria Andani; Risky Risky; Ilma Munaya; Muhammad Azman (Media Ilmiah Kesehatan Indonesia, 2026)
Vitamin C, or ascorbic acid, is a water-soluble vitamin with acidic properties and strong reducing capabilities. The content of vitamin C plays a role in protecting cells and molecules such as proteins, lipids, and nucleic acids, and it serves as an antioxidant that can neutralize free radicals in the body. The aim of this study was to identify the vitamin C content in fresh fruit such as sambal oranges and processed fruit such as passion fruit syrup, as well as to understand the stages involved in vitamin C testing. The testing was conducted using the iodometric titration method with a quantitative approach. The results showed that the vitamin C content in sambal oranges ranged from 0.179% to 0.219%, which was higher compared to passion fruit syrup, which had values ranging from 0.032% to 0.084%. These differences could be attributed to variations in the vitamin content of the fruits, their physical and chemical properties, and the technical aspects of the sample testing. Based on these results, sambal oranges and passion fruit syrup have the potential to serve as good sources of vitamin C, whether consumed directly or processed.